2003
DOI: 10.1182/blood-2001-12-0289
|View full text |Cite
|
Sign up to set email alerts
|

Novel epinephrine and cyclic AMP-mediated activation of BCAM/Lu-dependent sickle (SS) RBC adhesion

Abstract: The vasoocclusive crisis is the major clinical feature of sickle cell anemia, which is believed to be initiated or sustained by sickle (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
183
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 157 publications
(194 citation statements)
references
References 35 publications
8
183
1
2
Order By: Relevance
“…Evidence for activation of PKA was detectable in about half of the homozygous sickle cell patients we studied. Hines et al demonstrated recently that SS RBC from about 50% of patients could be stimulated by epinephrine via a PKA-dependent signaling pathway to increase B-CAM/LU-mediated adhesion [24]. While LD SS RBC were more responsive than HD SS RBC, when compared with their corresponding baselines, stimulated HD SS RBC still adhered to laminin more than did stimulated LD SS RBC [24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidence for activation of PKA was detectable in about half of the homozygous sickle cell patients we studied. Hines et al demonstrated recently that SS RBC from about 50% of patients could be stimulated by epinephrine via a PKA-dependent signaling pathway to increase B-CAM/LU-mediated adhesion [24]. While LD SS RBC were more responsive than HD SS RBC, when compared with their corresponding baselines, stimulated HD SS RBC still adhered to laminin more than did stimulated LD SS RBC [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that mature RBC have a number of signaling molecules and protein kinases, including protein kinase A and several tyrosine kinases [27]. A recent report also demonstrated that stimulation of a PKA-signaling pathway in vitro up-regulated B-CAM/LU-mediated adhesion to immobilized laminin during continuous flow [24]. We hypothesized that this pathway might be activated either in vivo or in response to shear stress in vitro.…”
Section: Evidence That Protein Kinase a Contributes To Increased Hd Smentioning
confidence: 91%
See 3 more Smart Citations